Odpowiedzi

2010-01-23T10:04:43+01:00
×-2γ=-6
3×-γ=-8 |*(-2)

x-2y=-6
-6x+2y=16
+________
5x=10 |:5
x=2

x=2
x-2y=-6

x=2
2-2y=-6

x=2
-2y=-6-2

x=2
-2y=-8 |:(-2)

x=2
y=4

Proszę o najjj :)
2010-01-23T10:06:28+01:00
×-2γ=-6 /:-2
3×-γ=-8

-½x+y=3 /+
3x-y=-8 /+

2½x=-5
x=-5 × ²/₅

x= -2

3 × -2 -y = -8

-6-y=-8
-y=-2
y=2

Odp. x=-2 y=2

Sprawdzenie, podstawiamy x=-2 oraz y=2
×-2γ=-6
3×-γ=-8

-2-2(2)=-6
3(-2)-2=-8

-2-4=-6
-6-2=-8

-6=-6
-8=-8

True ;)

P.S.
(...)
x-2y=-6
-6x+2y=16
+________
-5x=10 |:5
x=-2

(...)
itd.

Ale ja i tak się będę upierać, że -6x+x= -5x ;P

Moje krótsze ;)


2010-01-23T10:06:38+01:00
×-2γ=-6
3×-γ=-8 |*(-2)

x - 2y = -6
-6x + 2y =16

5x = 10
x = 2

x = 2
x - 2y = -6

x = 2
2 - 2y = -6

x = 2
-2y = -6 - 2

x = 2
-2y = -8

x=2
y=4